2005
DOI: 10.1002/jbm.a.30309
|View full text |Cite
|
Sign up to set email alerts
|

A novel osteotropic biomaterial OG‐PLG: Synthesis and in vitro release

Abstract: Statins (e.g., simvastatin) have shown to induce expression of the bone morphogenic protein-2 gene in bone cells, but they are not used clinically because of a lack of a suitable delivery device. The overall objective is to develop optimized statin delivery devices for bone regeneration. The specific objective was to determine the effect of grafting statins to biodegradable poly[lactide-co-glycolide] (PLG) on release kinetics. Simvastatin was grafted to PLG (OG-PLG) and characterized using contact-angle measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
(28 reference statements)
0
20
0
2
Order By: Relevance
“…In recent years, many researchers have investigated the utilization of statin, a drug that turns on the genes for bone formation, in bone grafting and found that this drug has tremendous osteoinductive effect and great promise in routine use in ridge augmentation and bone grafting in the craniofacial region [10][11][12][13][14]. Alternate materials and methods have been sought as effective bone graft substitutes because of various disadvantages of using autografts (the current gold standard) and allografts.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many researchers have investigated the utilization of statin, a drug that turns on the genes for bone formation, in bone grafting and found that this drug has tremendous osteoinductive effect and great promise in routine use in ridge augmentation and bone grafting in the craniofacial region [10][11][12][13][14]. Alternate materials and methods have been sought as effective bone graft substitutes because of various disadvantages of using autografts (the current gold standard) and allografts.…”
Section: Discussionmentioning
confidence: 99%
“…99 The slow release of the cholesterol-lowering drug simvastatin from degrading poly(lactide-co-glycolide) promotes bone mineralization of rat BMSCs more effectively than when the drug is dissolved in culture medium or even released by passive diffusion from scaffolds. 100 Advanced manufacturing techniques can be used to control the spatial architecture in engineered tissues, manipulating the scaffold topography on the length scale of the stem cell niche and smaller. Fused deposition modeling allows for the creation of computer-designed poly (caprolactone)/calcium phosphate scaffolds with honeycomblike 300-to 500-mm pores.…”
Section: Scaffoldsmentioning
confidence: 99%
“…When administered by injection their effect has been reported to be lost within 5 days 7) , making this modality impractical for clinical application in bone healing. Therefore, various methods of local administration, or drug delivery system (DDS), have been explored, and include the use of collagen gel, polyethylene glycol, and polylactide-co-glycolide [8][9][10] . One such carrier, gelatin-hydrogel, is biodegradable and already in use in various types of food and drug.…”
Section: Introductionmentioning
confidence: 99%